Mulheres moçambicanas: resistência, Associativismo, Feminismo - Santos, Aldenir Dias dos (2016)
The goal of this thesis is to understand the production of material life and the possible autonomy of women in southern Mozambique through the associative work in cooperatives of the General Union of cooperatives. The perspective is that the women are part of the population that is more vulnerable to economic, political and cultural issues, therefore, live in a situation of almost no negotiation with their spouse or other men in their family. This also means that they resist individually and in a collective form, through networks of solidarity and women's organizations. It is understandable that the historical experiences of autonomy and empowerment of women in Áfrican regions, as well as the recent economic and political history, of their country, are key to understanding how it is to live in Mozambique today. The field research was carried out in a one-stage sandwich abroad, by means of semi-structured interviews, a focal point group, the direct and indirect participant observation, in a partial inspiration of the method of Ethnography. The theoretical foundation go through the academic studies of sociology, political science and anthropology, and in this area, the way was more for the tools of the economy, as well as a field still under construction which is the Feminist Anthropology. The study concluded that the associative work of women generated income, which enabled forms of empowerment for themselves and their family, guaranteeing a certain autonomy in the management of their lives. As most of them live without their husband, they are themselves who take the responsibility in the management of organizations and in the management of the house, even where there is a spouse, i.e. their family leadership is independent of the existence of the man in the House. The thesis still inserts a perspective of intersectional feminism studies incorporating the diversity of being a woman